RISK FACTORS FOR RESPIRATORY DEATH AMONG INDONESIAN PILGRIMS IN 2018 - Prillia Safira Liani; Putri Bungsu Machmud (Universitas Airlangga, 2020)
Background: In 2018, respiratory disease was the leading cause of death in Hajj pilgrims, accounting for 37.40% of total deaths. Purpose: This study analyzes the most influential risk factors for death caused by respiratory disease among Indonesian pilgrims in 2018. Methods: This study uses a cross sectional design. Secondary data was obtained from the 2018 Integrated Hajj Computerized System for Health (Siskohatkes) and sourced from the Hajj Health Center (Puskeshaji), Ministry of Health of the Republic of Indonesia which is also recorded about the first to third Hajj medical examination records. The sample was all pilgrims who died while performing the Hajj in Saudi Arabia, 361 pilgrims. The variables included age, gender, pre-existing respiratory disease, education level, type of work, Body Mass Index (BMI), smoking status, and influenza vaccination status. The data was analyzed using chi square and multiple logistic regression. Results: The majority of pilgrims who died during the Hajj pilgrimage in Saudi Arabia in 2018 were aged ≥60 years (75.30%), male (58.40%), did not have a pre-existing respiratory disease (85.60%), had a low education level (46.00%), worked indoors (73.10%), had a normal BMI (48.20%), did not smoke (88.60%), and had had the influenza vaccine (56.20%). The most influential risk factors were pre-existing respiratory disease with PR = 1.55 (95% CI = 1.16 – 2.90) and influenza vaccination status with PR = 1.39 (95% CI = 1.07 – 1.81). Conclusion: Having a pre-existing respiratory disease and not being vaccinated against influenza increase the likelihood of respiratory disease death among Indonesian pilgrims in 2018.